Over a million students use our free study notes to help them with their homework
First we will differentiate the equation.To differentiate the equation we must multiply the coefficient by the power, and then subtract the power. If the is no x within an element the element become...
The probability of getting heads at least once is the same as saying the probability of getting heads: exactly once, exactly twice or exactly three times. This is also 1 minus the probability of getting ...
n(n+5)+2(n+3) = n2+5n+2n+6 = n2+7n +6 = (n+6)(n+1) = (n+6) x (n+1). The difference between (n+6) and (n+1) is 5, so this is a product of two numbers with a difference of 5.
First write out information from the question.s=4m u=0m/s v=? a=9.8m/s2 t=Choose correct "suvat" equation: v2=u2+2asSubstitute in known variables.Obtain v= 8...
(x + 1)/((x^2)*(2x – 1)) = -3/x - 1/x^2 + 6/(2x-1)
←
559
560
561
562
563
→
Internet Safety
Payment Security
Cyber
Essentials